Pre-Schoolers’ Parental Concern on Educational Effect of Information and Communication Technology on Children’s Learning - Kassim, Rafiah; Abu Samah, Siti Akmar (Mediterranean Journal of Social Sciences, 2021)
Technology has been the bread and butter of learning not only among school going children, but also those of pre-schoolers. Its access and usage has become the perennial tool to generate learning. Hence, it comes with the effects of the learning process. This study attempts to investigate the concern of pre-schoolers’ parents regarding the access of Information Communication Technology (ICT) that takes place both in school and at home. This has also become the cause of concern for parents as their children are exposed to its access and usage, conveniently 24/7. To conduct this study, questionnaires were given and duly completed by 10 parents in a small school of eighteen pre-schoolers. These pre-schoolers ranged from the ages of 3 to 6 years old. At these ages, the children have ICT knowledge, at home ranging from leisure games, electronic toys, mobile phones, television, CD, and computers. They have well educated parents with concerns on child computer addiction, health matters and lack of social values. Discussions on the findings focus on the advantages and disadvantages of technology access and usage among the pre-schoolers. They also included the questions on methods of access control or preventive measures to ensure safe ICT use for these pre-schoolers. This study took a qualitative approach as it was suitable to access the respondents’ perception and opinion via questionnaires. The analysis of the study results indicated that ICT had positive impact on education. The concern and setback for parents were the health issues, dark webs, and lack or over socialising. More often it is lack of social mingling.   Received: 27 June 2021 / Accepted: 9 August 2021 / Published: 5 September 2021